Comparing Treatment Plan in All Locations of Esophageal Cancer. Issue 17 (May 2015) - Lin, Jang-Chun; Tsai, Jo-Ting; Chang, Chih-Chieh; Jen, Yee-Min; Li, Ming-Hsien; Liu, Wei-Hsiu; He., Shihan
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to compare treatment plans of volumetric modulated arc therapy (VMAT) with intensity-modulated radiotherapy (IMRT) for all esophageal cancer (EC) tumor locations. This retrospective study from July 2009 to June 2014 included 20 patients with EC who received definitive concurrent chemoradiotherapy with radiation doses >50.4 Gy. Version 9.2 of Pinnacle3 with SmartArc was used for treatment planning. Dosimetric quality was evaluated based on doses to several organs at risk, including the spinal cord, heart, and lung, over the same coverage of gross tumor volume. In upper thoracic EC, the IMRT treatment plan had a lower lung mean dose (P = 0.0126) and lung V5 (P = 0.0037) compared with VMAT; both techniques had similar coverage of the planning target volumes (PTVs) (P = 0.3575). In middle thoracic EC, a lower lung mean dose (P = 0.0010) and V5 (P = 0.0145), but higher lung V20 (P = 0.0034), spinal cord Dmax (P = 0.0262), and heart mean dose (P = 0.0054), were observed for IMRT compared with VMAT; IMRT provided better PTV coverage. Patients with lower thoracic ECs had a lower lung mean dose (P = 0.0469) and V5 (P = 0.0039), but higher spinal cord Dmax (P = 0.0301) and heart mean dose (P = 0.0020), with IMRT compared with VMAT. PTV coverage was similar (P = 0.0858) for the 2 techniques. IMRT provided a lower mean dose and lung V5 in upper thoracic EC compared with VMAT, but exhibited different advantages and disadvantages in patients with middle or lower thoracic ECs. Thus, choosing different techniques for different EC locations is warranted.